Metal assisted catalyzed etched (MACE) black Si: optics and device physics. Issue 34 (17th August 2016) - Toor, Fatima; Miller, Jeffrey B.; Davidson, Lauren M.; Duan, Wenqi; Jura, Michael P.; Yim, Joanne; Forziati, Joanne; Black, Marcie R.
Abstract : This review provides an in-depth analysis of metal assisted chemical etching (MACE) and the commercial applications of this technology. Abstract : Metal-assisted catalyzed etching (MACE) of silicon (Si) is a controllable, room-temperature wet-chemical technique that uses a thin layer of metal to etch the surface of Si, leaving behind various nano- and micro-scale surface features, including nanowires (NWs), that can be tuned to achieve various useful engineering goals, in particular with respect to Si solar cells. In this review, we introduce the science and technology of MACE from the literature, and provide an in-depth analysis of MACE to enhance Si solar cells, including the outlook for commercial applications of this technology.